Regional Distributions of Iron, Copper and Zinc and Their Relationships With Glia in a Normal Aging Mouse Model - Ashraf, Azhaar; Michaelides, Christos; Walker, Thomas A.; Ekonomou, Antigoni; Suessmilch, Maria; Sriskanthanathan, Achvini; Abraha, Semhar; Parkes, Adam; Parkes, Harold G.; Geraki, Kalotina; So, Po-Wah (Frontiers in Aging Neuroscience, 2019)
Microglia and astrocytes can quench metal toxicity to maintain tissue homeostasis, but with age, increasing glial dystrophy alongside metal dyshomeostasis may predispose the aged brain to acquire neurodegenerative diseases. The aim of the present study was to investigate age-related changes in brain metal deposition along with glial distribution in normal C57Bl/6J mice aged 2-, 6-, 19- and 27-months (n=4/age). Using synchrotron-based X-ray fluorescence elemental mapping, we demonstrated age-related increases in iron, copper and zinc in the basal ganglia (p<0.05). Qualitative assessments revealed age-associated increases in iron particularly in the basal ganglia and zinc in the white matter tracts, while copper showed overt enrichment in the choroid plexus/ventricles. Immunohistochemical staining showed augmented numbers of microglia and astrocytes, as a function of aging, in the basal ganglia (p<0.05). Moreover, qualitative analysis of the glial immunostaining at the level of the fimbria and ventral commissure, revealed increments in the number of microglia but decrements in astroglia, in older aged mice. Upon morphological evaluation, aged microglia and astroglia displayed enlarged soma and thickened processes, reminiscent of dystrophy. Since glial cells have major roles in metal metabolism, we performed linear regression analysis and found a positive association between iron (R2=0.57, p=0.0008), copper (R2=0.43, p=0.0057), zinc (R2=0.37, p=0.0132) with microglia in the basal ganglia. Also, higher levels of iron (R2=0.49, p=0.0025) and zinc (R2=0.27, p=0.040) were correlated to higher astroglia numbers. Aging was accompanied by a dissociation between metal and glial levels, as we found through the formulation of metal to glia ratios, with regions of basal ganglia being differentially affected. For example, iron to astroglia ratio showed age-related increases in the substantia nigra and globus pallidus, while the ratio was decreased in the striatum. Meanwhile, copper, zinc, and calcium to astroglia ratios showed a similar regional decline. Our findings suggest that inflammation at the choroid plexus, part of the blood-cerebrospinal-fluid barrier, prompts accumulation of, particularly, copper and iron in the ventricles, implying a compromised barrier system. Moreover, age-related glial dystrophy/senescence appears to disrupt metal homeostasis, likely due to induced oxidative stress, and hence increase the risk of neurodegenerative diseases.